2017
DOI: 10.2490/prm.20170013
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of the Postural Vertical in Healthy Participants

Abstract: Objective:The aim of the present study was to determine the test-retest reliability of the angle of subjective verticality in healthy young persons. Methods: The participants were ten young healthy adults, five men and five women. The subjective postural vertical (SPV) was measured in the frontal plane (with eyes open and eyes closed) and in the sagittal plane (with eyes closed). Participants were retested 1 week after the first test. The test-retest reliability for each parameter was estimated using the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Karnath et al [11] and Fukata et al [16] reported that the VP of patients with Pusher syndrome was biased toward the nonparetic or paretic side. Moreover, bilateral bias existed even in healthy participants [22][23][24]. In this study, the VP of the participants was biased to the non-paretic or paretic side, which may have prevented deviation of the total mean value.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Karnath et al [11] and Fukata et al [16] reported that the VP of patients with Pusher syndrome was biased toward the nonparetic or paretic side. Moreover, bilateral bias existed even in healthy participants [22][23][24]. In this study, the VP of the participants was biased to the non-paretic or paretic side, which may have prevented deviation of the total mean value.…”
Section: Discussionmentioning
confidence: 78%
“…Fujino et al [24] reported that the minimal detectable change with 95% con dence (MDC 95 ) in the SPVs of healthy participants was 1.2°. Similarly, the improvement in SPV variability errors was 2.1° after 1 month in group B in this study, which is above the MDC 95 , indicating that the true improvement in SPV variability errors occurred only in group B after 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the VP of participants was biased toward the nonparetic or paretic side, which may have prevented the deviation of the total mean value. Fujino et al (2017) reported that the minimal detectable change with 95% confidence (MDC 95 ) in the SPVs of healthy participants was 1.2 • . Similarly, in this study, the improvement in SPV variability errors was 2.1 • after 1 month in the deviation of variability errors group, which is above the MDC 95 , indicating that true improvement in SPV variability errors occurred only in the deviation of variability errors group after 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Sawa et al., 2022; Fukata et al., 2020; Karnath et al., 2000) have reported that the VP of patients with Pusher syndrome was biased toward the nonparetic or paretic side. Moreover, bilateral bias existed even in healthy participants (Baggio et al., 2016; Fujino et al., 2017). In this study, the VP of participants was biased toward the nonparetic or paretic side, which may have prevented the deviation of the total mean value.…”
Section: Discussionmentioning
confidence: 99%
“…When the participant was exposed to visual flow, the CoP data was recorded, and the Standard Deviation (σ) of CoP was calculated [51]. The value of σ represents the dispersion of the CoP.…”
Section: Postural Sway (Cop Oscillation)mentioning
confidence: 99%